Peran Pendidikan Agama Islam dalam Penguatan Karakter Religius Ditengah Kultur Globalisasi - Zahro, Aulia; Muna, Nailil; Oktavia, Dita; Muhlisin, Muhlisin; Mafaakhir, Abul (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Globalization influences various aspects of life. One impact of globalization is the ease of access to information technology, which also influences moral and character issues. Islamic education is a strategic effort in shaping religious character in response to the challenges of the globalization era. This study aims to examine the role of Islamic Religious Education as a strategic step in strengthening religious character to face the challenges of globalization. The method used is a literature study with a qualitative approach, analyzing phenomena, concepts, and theories based on literature such as books, journals, and articles relevant to the research topic. The main findings of this study indicate that Islamic Religious Education has the potential to build religious character as a provision to face the impact and influence of global culture. This study identifies obstacles in strengthening religious character through Islamic Religious Education and offers solutions and strategies to strengthen that character. The implications of this study emphasize the importance of responding to moral and character issues in the era of globalization with an adaptive approach through solutions and strategies of Islamic Religious Education.